Implementation of the Numbered Head Together (NHT) Type of Cooperative Model Assisted by Trello Application in Sport Health Education Courses Penjas FKIP UNIB - Bogy Restu Ilahi; Yarmani Yarmani; Septian Raibowo; Tono Sugihartono; Fina Hiasa (UNIB Press, 2023)
Sports Health Education uses the Agile Scrum Trello Application as a learning medium in the application of the Number Head Together (NHT) model to the fifth semester students of the Physical Education Study Program, FKIP University of Bengkulu. This research shows that the combined use of Agile Scrum and Trello can be continuously maintained and practiced by information system developers. The combination of the two is quite reliable, with the use of Trello, and implemented into the Cooperative model of Number Head Together (NHT) type, collaboration between teams is more harmonious and task tracking is easier. This research is a classroom action research that uses this descriptive method and will be carried out in two cycles. Where data collection is done through test and non-test techniques. As a result, the achievement targets were obtained in cycle II with the following details; 15 students or 42% got category A, 17 students or 47% got category B, 4 students or 11% got category C, and none or 0 students got category D. The results of the questionnaire responses distributed to students showed they gained the final score of 24.61 or obtained an average of 4.1 which means the category most chosen by students is agreed. These results indicate that the implementation of learning in the application of the Number Head Together (NHT) model to the fifth semester students of the Physical Education Study Program, FKIP University of Bengkulu, is of interest to students.